1998
DOI: 10.1002/(sici)1521-186x(1998)19:2<117::aid-bem10>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to a 60 Hz magnetic field affects rats' water-maze performance

Abstract: Rats were trained in six sessions to locate a submerged platform in a circular water‐maze. They were exposed to a 1 mT, 60 Hz magnetic field for one hour in a Helmholtz coil system immediately before each training session. In addition, one hour after the last training session, they were tested in a probe trial during which the platform was removed and the time spent in the quadrant of the maze in which the platform was located during the training sessions was scored. Control animals were sham‐exposed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…In these studies using rats and mice, animals who had been exposed at 0.75 mT for 45 min before testing made signi®cantly more errors in a radial arm maze than control animals during performance of a food-reinforced task [Lai, 1996;Sienkiewicz et al, 1998aSienkiewicz et al, , 1998b although in the case of the mice at least, overall accuracy was not impaired, and the ®nal levels of performance were comparable to the control animals [Sienkiewicz et al, 1998a]. Further evidence for an effect of magnetic ®elds on spatial memory comes from a recent study using a Morris water maze [Lai et al, 1998]. Rats which had been exposed at 1 mT for 1 h before training demonstrated poorer retention of the location of the escape platform during the probe trial, although initial acquisition of the place learning task was unaffected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies using rats and mice, animals who had been exposed at 0.75 mT for 45 min before testing made signi®cantly more errors in a radial arm maze than control animals during performance of a food-reinforced task [Lai, 1996;Sienkiewicz et al, 1998aSienkiewicz et al, , 1998b although in the case of the mice at least, overall accuracy was not impaired, and the ®nal levels of performance were comparable to the control animals [Sienkiewicz et al, 1998a]. Further evidence for an effect of magnetic ®elds on spatial memory comes from a recent study using a Morris water maze [Lai et al, 1998]. Rats which had been exposed at 1 mT for 1 h before training demonstrated poorer retention of the location of the escape platform during the probe trial, although initial acquisition of the place learning task was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to suggest that the processing of spatial information in adult animals can be affected by exposure to speci®c combinations of static and time-varying ®elds at about 50 mT [Creim et al, 1990;Lovely et al, 1991Lovely et al, , 1992Lovely et al, , 1993Lovely et al, , 1994Cheryshev et al, 1997], and by exposure to power frequency ®elds at 100 mT [Kavaliers et al, 1993[Kavaliers et al, , 1996Lai, 1996;Lai et al, 1998;Sienkiewicz et al, 1998aSienkiewicz et al, , 1998b. Both increases and decreases in learning pro®ciency have been reported, although some studies have failed to ®nd any signi®cant ®eld-dependent effects Sienkiewicz et al,1996].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lai [3] reported that exposure to 1 mT, 60-Hz magnetic field (MF) for 1 h immediately before each training session of the Morris water maze test impaired the spatial memory retention. Likewise, in radial maze test, exposure to 0.45 mT ELF MF for 45 min shortly before daily testing sessions reduced the acquisition rate of spatial learning task [1].…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is also possible that the effects of MRI exposure on memory performance may be due to effects of the magnetic field on the cholinergic system. Lai and his colleagues (Lai et al, 1998;Lai et al, 1993) Fig. (3).…”
Section: Discussionmentioning
confidence: 99%